2014
DOI: 10.1523/jneurosci.1260-14.2014
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of miR-23a and miR-27a following Experimental Traumatic Brain Injury Induces Neuronal Cell Death through Activation of Proapoptotic Bcl-2 Proteins

Abstract: MicroRNAs (miRs) are small noncoding RNAs that negatively regulate gene expression at the post-transcriptional level. To identify miRs that may regulate neuronal cell death after experimental traumatic brain injury (TBI), we profiled miR expression changes during the first several days after controlled cortical impact (CCI) in mice. miR-23a and miR-27a were rapidly downregulated in the injured cortex in the first hour after TBI. These changes coincided with increased expression of the proapoptotic Bcl-2 family… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
123
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 136 publications
(130 citation statements)
references
References 58 publications
4
123
1
Order By: Relevance
“…Neither TBI nor central administration of miR-711 hairpin inhibitor changed the levels of APAF1, cytochrome c and AIF-1 in whole cell lysates after TBI (data not shown), which is consistent with our previous results. 20 Western blot revealed that TBI induced the release of cytochrome c and AIF-1 from mitochondria to the cytoplasm, and AIF-1 translocation to nucleus (Figures 6a and b). Treatment with miR-711 hairpin inhibitor significantly reduced TBI-induced release of AIF-1 and cytochrome c into the cytosol and the level of AIF-1 in the nucleus (Figures 6a and b).…”
Section: Mir-711 Activates Neuronal Apoptosis B Sabirzhanov Et Almentioning
confidence: 99%
See 4 more Smart Citations
“…Neither TBI nor central administration of miR-711 hairpin inhibitor changed the levels of APAF1, cytochrome c and AIF-1 in whole cell lysates after TBI (data not shown), which is consistent with our previous results. 20 Western blot revealed that TBI induced the release of cytochrome c and AIF-1 from mitochondria to the cytoplasm, and AIF-1 translocation to nucleus (Figures 6a and b). Treatment with miR-711 hairpin inhibitor significantly reduced TBI-induced release of AIF-1 and cytochrome c into the cytosol and the level of AIF-1 in the nucleus (Figures 6a and b).…”
Section: Mir-711 Activates Neuronal Apoptosis B Sabirzhanov Et Almentioning
confidence: 99%
“…20 Although Bcl2 family molecules are not among miR-711-predicted targets, Akt is such a target. 26 Akt (protein kinase B) can attenuate neuronal apoptosis through phosphorylation and inhibition of caspases, pro-apoptotic Bcl2 family molecules and selected transcription factors (FoxO3a).…”
Section: Mir-711 Activates Neuronal Apoptosis B Sabirzhanov Et Almentioning
confidence: 99%
See 3 more Smart Citations